Impact of UV-C irradiance and wavelength on the photodegradation of dibromoacetonitrile - Lohita Rajesh; Joshua Fiorentino; Thomas Roberts; Sean T. McBeath; Mariana Lanzarini-Lopes (Environmental Advances)
Ultraviolet-C (UV-C) irradiation is practiced at the point-of-use and point-of-entry as a last barrier disinfection strategy. Interaction between UV-C light and chlroinated drinking water can result in photo-induced transformation and remediation of disinfection by-products (DBPs). The study investigates how engineering design factors (such as the wavelength and irradiance of UV-C LEDs) and experimental parameters (such as solvent and reactor volume) affect the degradation kinetics of a photolyzable nitrogenous DBP, dibromoacetonitrile (DBAN). UV-C LEDs with characteristic peak wavelengths of 265, 275, and 280 nm and output power of 32–40 mW were studied to degrade DBAN, where acetone and methyl tert-butyl ether (MtBE) were used as the preparation solvents. Quantum yield fluence-based kinetic rate constants (kf), and electrical energy per order (EEO) were calculated for different experimental conditions. EEO was inversely related to quantum yield and lowest for the 265 nm high-power UV-C LED at 80.43 kWh/m3. A significant finding is that incident irradiance greatly impacted the degradation kinetics even when normalized by fluence. The 265 nm high-power LED resulted in 2.3-times higher quantum yield and fluence-based degradation kinetics than the 265 low-power LED and a corresponding 3.5 times lower EEO despite the same wavelength of irradiance. Lastly, we demonstrate that the solvent selected significantly impacts kinetics, where the degradation of DBAN with acetone is 2.28-times greater than with MtBE at the 275 nm wavelength. Indirect photochemical reactions increase observed degradation kinetics; therefore, solvents should be carefully selected for photochemical studies targeting water treatment. This study provides key insights to engineers, as well as an understanding of the impact of UV-C-based POU treatment design for drinking water systems.